Bicentric evaluation of Access Toxo immunoglobulin M (IgM) and IgG assays and IMx toxo IgM and IgG assays and comparison with Platelia Toxo IgM and IgG assays. - Decoster, A (1996)
The recent Access immunoanalysis system (Sanofi Diagnostics Pasteur) for the serological diagnosis of toxoplasmosis was compared with the Abbott Toxo IMx EIA system, taking the Platelia Toxo immunoglobulin G (IgG) and Platelia Toxo IgM systems as references and using as confirmation methods an indirect fluorescence assay or a dye test for IgG and an immunosorbent agglutination assay (ISAGA) for IgM. A total of 1,461 serum samples were studied, of which 128 were collected from 42 recently seroconverted patients. Sensitivity and specificity rates of the Access system were 97.7 and 99.5%, respectively, for IgM and 98.6 and 100%, respectively, for IgG. Sensitivity and specificity rates of the Abbott IMx EIA system were 91 and 100%, respectively, for IgM and 92.5 and 100%, respectively, for IgG. The Access Toxo IgG and IgM EIA systems were found to be more sensitive than the Abbott Toxo IgG and IgM IMx EIA systems.